Romanian consumer profile of PlayStation games - Adriana Manolică; Nicoleta-Bianca Bincă; Teodora Roman (CES Working Papers, 2021)
PlayStation is the market leader of the console industry, with over 90 million active users registered on their platform. It is a remarkable feat to appeal to so many consumers and keep them interested. This study reveals the results of an online survey on 600 Romanian PlayStation console users. The Romanian consumer is loyal, perceiving longevity with the brand as stability and which will encourage their level of loyalty to increase. The main disparity between the Romanian and foreign consumer lies in the average monthly income, which, however, does not hinder the former's buying intention, pointing towards a tendency to sacrifice other needs in order to fulfil playing experience and desires. The study has revealed a complex characteristic behaviour which shapes and constructs the consumer profile of the Romanian PlayStation user.
Keywords: 330; PlayStation console; customer loyalty; customer retention; customer profile